Swelling Prediction of Expansive Soil Using Numerical Method Analysis - Diaz Ishak; Wirman Hidayat; Rangga Adiprima Sudisman; Arlyn Aristo (Indonesian Geotechnical Journal, 2022)
Expansive soil is one of the factors that cause road damage in Indonesia. Its behavior is influenced by moisture content. At high moisture content, expansive clay has a very low bearing capacity and high swelling and shrinkage rate compared to other soil types. This soil expansion causes a heave force on the road pavement. When the force exceeds the strength of the pavement, the pavement will deform and break as the initial damage is created. Therefore, it is critical to investigate the effect of moisture content on the swelling-shrinkage behavior of expansive soil. In this study, soil expansion is numerically predicted using the finite element approach on ABAQUS compared to the laboratory expansion index test. The geometric shape and loading of the soil model are the same as the sample shape and loading of a laboratory expansion index test. The Mohr-Coulomb soil constitutive model with sorption is used to simulate water absorption in partially saturated soils. Coupled wetting liquid flow and porous medium stress analysis are used to simulate swelling and shrinkage. The simulation is divided into two types: geostatic, which simulates soil model loading, and coupled pore fluid, which simulates changes in water content. The simulation is then compared to the laboratory test for validation. The numerical analysis results show that the model's accuracy depends highly on the constitutive soil model, whereas the Mohr-Coulomb model shows a limitation in accuracy with the maximum swelling in the simulation is 21.704%, while the average maximum swelling in laboratory testing is 15.515%.